WHAT IS NEGATIVE ENTROPY AND HOW DOES IT AFFECT THE SUSTAINABILITY OF REGIONS DURING THE WARFARE - Pershina, Katherine (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2022)
The impact of warfare in one region on other regions is shown using the base fundamental thermodynamics laws and trends of decreasing entropy. The physical sense of the negentropy is described use of the principles of chemical thermodynamics. A phenomenological model for the description impact of warfare on the ecological part of the region is proposed. According to this model, a system without plants, with destroyed soils, can't be alive without external factors. Based on thermodynamic differences between turbulent and laminar flows, the capability of the zones formation with an absence of the ability to any own functioning outside zone with military actions is shown. With the rising number of influencing factors, especially in large areas, the probability of narrowing and loss of zones with a stable state as in the region with military action but in neighboring regions increases.